2015
DOI: 10.1097/md.0000000000001592
|View full text |Cite
|
Sign up to set email alerts
|

Network Meta-Analysis Comparing Relatively Selective COX-2 Inhibitors Versus Coxibs for the Prevention of NSAID-Induced Gastrointestinal Injury

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
15

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 54 publications
0
21
0
15
Order By: Relevance
“…Analgesic drugs are used in relieving pain caused by various inflammatory disorders, but they do not reduce the pain in the heart, liver and kidney. Usage of this drug in a therapeutic dosage is beneficial and advisable for health, but on frequent usage and in higher doses it would lead to the damage of various organs in the body (Yang et al ., ). Each day about 30 million of the world's population are using NSAIDs.…”
Section: Non‐steroidal Anti‐inflammatory Drugsmentioning
confidence: 97%
See 1 more Smart Citation
“…Analgesic drugs are used in relieving pain caused by various inflammatory disorders, but they do not reduce the pain in the heart, liver and kidney. Usage of this drug in a therapeutic dosage is beneficial and advisable for health, but on frequent usage and in higher doses it would lead to the damage of various organs in the body (Yang et al ., ). Each day about 30 million of the world's population are using NSAIDs.…”
Section: Non‐steroidal Anti‐inflammatory Drugsmentioning
confidence: 97%
“…In leukocytes, diclofenac reduces the intracellular content of amino acids (Yang et al ., ). Various studies have reported the effects of diclofenac that would lead to hepatitis and hepatotoxicity (Gómez‐Lechón et al ., ).…”
Section: Diclofenacmentioning
confidence: 99%
“…COX‐1 promotes production of the mucosal lining, which serves to protect the gastrointestinal (GI) tract. Inhibition of COX‐1 increases the potential risk of GI side effects [9,10]. COX‐1 inhibition also decreases synthesis of thromboxane in platelets, thereby interfering with platelet aggregation, which confers an increased bleeding risk [9,10].…”
Section: Nsaid Pharmacologymentioning
confidence: 99%
“…Закономерно было бы предположить, что использование высокоселективных коксибов сопровождалось еще большим ростом безопасности со стороны ЖКТ. Действительно, применение высокоселективных ингибиторов ЦОГ-2 (коксибов) уменьшало риск развития гастродуоденальных язв (снижение относительного риска на 74%) и язвенных осложнений (снижение на 61%) по сравнению с неселективными НПВП [14]. Однако, как часто бывает в медицине, дальнейший рост селективности в отношении ЦОГ-2, не сопровождался значимым увеличением безопасности в отношении ЖКТ.…”
Section: Conflict Of Interestunclassified